1.1 Information, analytical and accounting support for management decision-making - Illiashenko, Kateryna; Ілляшенко, Катерина Володимирівна; Илляшенко, Екатерина Владимировна; Bezverkhnya, Yuliia; Безверхня, Юлія Вікторівна; Безверхняя, Юлия Викторовна (Primedia eLaunch, 2020)
The activity of any enterprise and its success in the market depends on many environmental factors. That is why each organization in the framework of management implements the planning function, collecting and analyzing information about the conditions of doing business. Planning helps the organization make decisions that prevent the occurrence and development of problem situations, without compromising the achievement of organizational goals.
Keywords: planning; information; consulting services; the collection; support of management decisions; methods of expert assessments; collection